Mutation burden in patients with small unrepaired atrial septal defects - Anne Kathrine Møller Nielsen (International Journal of Cardiology Congenital Heart Disease, 2021)
Background: In a recent nationwide cohort study, we have discovered that patients living with an atrial septal defect (ASD) have a shorter life expectancy, increased risk of atrial fibrillation, pneumonia, and psychiatric issues compared to the general population. The pathophysiological mechanisms are still unknown. The objective of this study is to investigate if this group of patients is burdened by mutations in genes associated with ASD. Methods: We included 147 patients with an unrepaired ASD. We curated a list of ASD candidate genes, and patients were analyzed for genetic variants in these genes, using targeted next generation sequencing. We filtered for protein altering variants (PAVs) and protein truncating variants (PTVs) with minor allele frequency (MAF) < 0.01 and we predicted pathogenicity using the Combined Annotation Dependent Depletion (CADD) method. The number of rare and pathogenic variants in cases were compared with variants identified in 33,370 controls of European ancestry. Results: We identified 384 rare (MAF<0.01) PAVs, including 41 PTVs, in 59 genes. ASD patients were significantly enriched for very rare (MAF<0.0001) PAVs compared to controls (P = 0.0001). The frequency of PAVs with CADD score ≥30 was significantly higher in ASD patients, compared to controls (P = 0.0042). Conclusions: Patients with a small, unrepaired ASD were enriched for rare PAVs within 59 ASD candidate disease genes. Our results suggest that recurrence risk of congenital heart defects in offspring may be increased for this group of patients and warrants further investigations.